Water, Sanitation, and Hygiene in Indonesia School: Facilities and Infrastructure Availability - Devi Angeliana Kusumaningtiar; Erna Veronika; Veza Azteria; Taufik Rendi Anggara (Gonabad University of Medical Sciences, 2024)
Background: One of the sustainable development goals (SDGs) is universal access to clean water and basic sanitation by 2030. Water, sanitation, and hygiene (WASH) support SDG targets such as eliminating poverty and improving health and education. Methods: The sample of this study amounted to 30 schools consisting of 10 elementary schools, 10 junior high schools, and 10 senior high schools. Sampling was based on stakeholder decisions on several issues related to washing. Results: This study was conducted by directly observing schools regarding the amount of drinking water, number of toilets, bathrooms, handwashing facilities alone, and handwashing facilities with water and soap. The results showed that elementary and junior high schools have insufficient toilet facilities and low handwashing facilities with water and soap. The average number of handwashing facilities with water and soap in schools in Bekasi City, Indonesia, was 1 for elementary schools, followed by junior high schools and high schools for 4-5 points. Conclusion: As soap is still unavailable in many Bekasi City schools, and there are inadequate handwashing facilities, it is recommended that handwashing facilities must be available with soap and water.